FAKTOR-FAKTOR YANG MEMPENGARUHI IBU HAMIL DALAM MEMILIH PENOLONG PERSALINAN - Ratna Malawat; Viqy Lestaluhu; Meilany Laisouw (Poltekkes Kemenkes Maluku, 2023)
Utilization of delivery assistance by professional staff (midwives) in the community is very low compared to the expected indicators. The behavior of pregnant women in planning for the selection of delivery assistance is influenced by various factors. This study aims to determine the factors associated with the selection of birth attendants. The type of research used is quantitative with a cross-sectional research design. The number of samples taken was 42 people with the Consecutive Sampling technique. The instrument used is a questionnaire. The data obtained was then analyzed with the Chi Square test. The results showed that there was a significant relationship between education and the selection of birth attendants (p value = 0.005). In addition, there is a significant relationship between parity and age and the selection of birth attendants (p value = 0.033 and p value = 0.025). Therefore, it is hoped that health workers can provide counseling related to the selection of birth attendants so that they can improve the health status of mothers and babies.